Crystal structure of paliperidone, C23H27FN4O3. Issue 2 (29th March 2016) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of paliperidone has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Paliperidone crystallizes in space group P 21 / n (# 14) with a = 14.151 58(6), b = 21.537 80(9), c = 6.913 26(2) Å, β = 92.3176(2)°, V = 2105.396(13) Å 3, and Z = 4. The unit-cell volume at 295 K is 1.5% larger than at 200 K, but the expansion is anisotropic; the b -axis is nearly constant at the two temperatures, while the a - and c -axes expand by 0.71 and 0.87%, respectively. There is only one significant hydrogen (H)-bond in the crystal structure. This H-bond is between the hydroxyl group O31–H58 and the ketone oxygen O25. The result is a chain along the c -axis with graph set C1, 1(7). In addition to this H-bond, the molecular packing is dominated by van der Waals attractions. The powder pattern is included in the Powder Diffraction File ™ as entry 00-064-1497.